Eurasian Civilization: from an Idea to a Modern Discourse - I. F. Kefeli (Евразийская интеграция: экономика, право, политика, 2021)
The article traces the evolution of the Eurasian idea, starting from the initial stage of its formation, in the context of comparing it with the implementation of the Soviet project in the pre-war years on the basis of the first three five-year plans for socialist construction. Attempts to formalize the theoretical status of the Eurasian civilization were formed on the basis of ideas about “Russia–Eurasia” as a cultural personality, about the Eurasian state, often comparing these constructions with the real achievements of socialist construction and confidently declaring the Eurasian world order within Russia–Eurasia in the future.